Emotion Regulation and Job Satisfaction Among Persons with Visual Impairment Working in Jordanian Society during the COVID-19 Pandemic - Abumelhim, Mohammad; Abu-Alkeshek, Esra’a (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aimed to assess the levels of emotional regulation and job satisfaction among individuals with visual impairment working in Jordanian society during the COVID-19 pandemic, and explore the relationship between these variables. Methods: The study employed a descriptive correlational approach and utilized two measurement tools: emotional regulation measurement and job satisfaction measurement. The sample consisted of 156 employees with visual impairment. Results: The study yielded several findings. First, there was an increase in the level of emotional regulation among the study participants. Additionally, the level of job satisfaction among the sample members was found to be at a moderate level. Moreover, the study revealed a statistically significant positive relationship between the domains of emotional regulation, job satisfaction, and their respective overall scores. Conclusions: Based on the findings, a key recommendation of this study is to reconsider the rewards and incentives provided by the institutions where individuals with visual impairment are employed.